Bioacessibilidade e biodisponibilidade de compostos fenólicos de sementes de Triplaris Gardneriana Wedd (Polygonaceae) - Lopes Neto, José Joaquim (2017)
Triplaris gardneriana Wedd is a plant species from Brazilian semiarid region with seeds rich in phenolic compounds and high antioxidant capacity.The consumption of fruits and vegetables has been associated to low incidence of chronic diseases caused by oxidative stress. Among the food components capable of combating excess free radicals arethe phenolic compounds, with antioxidant capacity, which have been extensively studied. However, the total quantity of these substances present in foods does not necessarily reflect the bioactive amount absorbed and metabolized by the body. In this context, the present work aimed the development of an ethanolic extract obtained from the seeds of T. gardneriana (EETg), and from this, to evaluate its antioxidant activity through different methodologies, to investigate the bioaccessibility of EETg by determination of phenolic composition before and after in vitro digestion as well as to estimate its indirect bioavailability by chemical analysis of plasma and urine in rodents after oral administration. In general, EETg presented levels of antioxidant activity by DPPH, ABTS.+, FRAP and TBARS tests comparable to those described in specialized literature. The bioaccessibility indexes of phenolic compounds in EETg were 48.65 and 69.28% in the presence and absence of enzymes, respectively. Among the identified phenolics classes, flavonoids, represented by galloylated procyanidins, proved to be more bioaccessible (81.48 and 96.29% in the post-intestinal phase with and without enzymes, respectively). The oral administration in Wistar rats resulted in a significant decrease in plasma total antioxidant capacity (TAC) by FRAP assay 4 h after beginning the experiment. As to urine analysis, an increase in TAC by DPPH and FRAP was observed from 1 and 4 h after administration, respectively. UPLC-QTOF analysis of urine detected 2 metabolites originated from the degradation of phenolic compounds: hippuric acid and phenylacetil glycine. These results suggest that phenolic compounds in T. gardneriana, despite their antioxidant potential, are unstable under gastrointestinal conditions, being flavonoids the components with higher bioaccessibility; besides that, they showed limited bioavailability due to their rapid biotransformation and urinary elimination.